PENGGUNAAN METODE DISKUSI DAN MEDIA GAMBAR DALAM PEMBELAJARAN TENTANG KEDUDUKAN DAN PERAN ANGGOTA KELUARGA UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS II PADA SD NEGERI 35 PINCURAN VII - ASMIWATI ASMIWATI (JURNAL MANAJEMEN PENDIDIKAN, 2019)
Social Sciences subject is one of the main subjects given at all levels of the school because it is related to daily life. This condition also occurs in grade II students of SDN 35 Pincuran VII, Tanah Datar Regency, with 21 students still lacking social sense. In this case students need to be confronted with real (concrete) reality. From the observations of the improvement of Social Science learning material "The Position and Role of Family Members" through the discussion method carried out in two stages, namely cycle I and cycle II, it can finally be concluded that the implementation of the learning process carried out by a teacher using the discussion method is interesting student interest which can ultimately increase learning achievement. As in the implementation of the improvement of learning in class II semester 2 SDN 35 Pincuran VII Tanah Datar District 2014/2015 school year